2020
DOI: 10.5530/jyp.2020.12.76
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Knowledge and Awareness about Biosimilars in Saudi Arabia: What is Imperative to Know ??

Abstract: Objectives: This study determined the current awareness and knowledge among physicians about biosimilars in Saudi Arabia. Methods: This study used a cross-sectional study design and data were acquired by the convenience sampling method. The research tool was self-developed, prevalidated and self-administered to achieve the sample size. The physicians from various parts of the country participated in the study. Both, inferential statistics with the help of descriptive statistics were applied using the Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…These results are rational as biosimilar formulations are a relatively new therapy approach whereby numerous healthcare professionals are not thoroughly familiar with. [19][20][21][22][23] Our study results are in contrast with Iga Pawłowska et al and Joan O'Callaghan et al who reported that the majority of the pharmacists in their studies expressed greater familiarity with biosimilar medications and their uses. 8,24 Moreover, the findings from many other similar studies from different parts of the world like New Zealand, the USA, Ireland, and the UK suggest that the majority of the healthcare professionals, especially pharmacists had adequate knowledge about biosimilar medications and their benefits, but still there are several knowledge and attitude gaps regarding biosimilar medications.…”
Section: Discussioncontrasting
confidence: 97%
“…These results are rational as biosimilar formulations are a relatively new therapy approach whereby numerous healthcare professionals are not thoroughly familiar with. [19][20][21][22][23] Our study results are in contrast with Iga Pawłowska et al and Joan O'Callaghan et al who reported that the majority of the pharmacists in their studies expressed greater familiarity with biosimilar medications and their uses. 8,24 Moreover, the findings from many other similar studies from different parts of the world like New Zealand, the USA, Ireland, and the UK suggest that the majority of the healthcare professionals, especially pharmacists had adequate knowledge about biosimilar medications and their benefits, but still there are several knowledge and attitude gaps regarding biosimilar medications.…”
Section: Discussioncontrasting
confidence: 97%
“…This study has assessed the pharmacists' knowledge level and views about biosimilar medicines in Jordan and to explore the predictors which could influence their knowledge. Few surveys have been conducted to assess pharmacists' knowledge and attitude toward biosimilars in Middle-East countries [ 26 , 27 ], and up to our knowledge this is the first questionnaire survey that has been conducted in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is a lack of published data about the awareness and the knowledge of physicians about biosimilars [10]. So, the aim of this study was to investigate physicians' opinions on the required information about biosimilars and the need for biosimilars related education.…”
Section: Introductionmentioning
confidence: 99%